Vertical Integration in the Russian Federation: From Mine to Consumer – Business Plan for Choron group - Mehta, Aadil (2009)
Abstract Jewelry market belongs to the luxury markets, which boomed through most of 2003 to 2007. Recently, of course, there has been a steep down slide in the industry and companies are looking out for innovative strategies to get back on the growth trajectory. Over the past few decades there has been a strong demand from the developed countries of emotion-inducing luxury items like jewelry. Developing countries are predicted to avidly catch up. Leaving the current economic turmoil aside, Russia is a wonderful example of a country where rapid economic development has enriched its citizens with both new necessities as well as financial means to satisfy them. Unfortunately, it has been seen that local jewelry producers often lag behind and at best respond to consumer needs instead of envisioning and directing them. Jewelry market is especially sensitive due to its relatively high prices, importance of trust and associated emotions. The local producers haven’t been able to match the market expectations perfectly even though Russia is generously gifted with precious stones and metals and has a long history of fine jewelry making. Currently, the market needs a strong brand with admirable products, reasonable prices, developed retail network and, most importantly, an efficient communication strategy. Choron has what it would take to succeed in the Russian market. With a strong manufacturing history and set up, wealth of experience in the diamond business and firsthand experience of selling branded jewelry in the last 5 years. Thus, Choron needs to look forward to develop a strategic expansion plan. Therefore a chance to formulate a business plan for Choron seemed like an interesting proposition. However, to formulate the business plan, a lot of necessary ground work had to be created. The project was divided into 3 main parts. The first part would focus more on the motivations, methodology and the theoretical concepts reviewed while conducting the research and formulating the business plan. The second part would dwell into various aspects and attributes of the Russian Jewelry market 5 MBA‐ Entrepreneurship Management Project‐ Part 1 2009 through the data unearthed by the conduction of an extensive research. Research: The main objective of the research was to gain marketing information to develop the strategy for promoting Choron Diamond on the Russian market. The research aimed at discovering various facets of the Russian Jewelry market which would in turn help strategizing and validating the aggressive expansion plans that the company had in mind. A comprehensive desk research and in-depth interviews with key stake holders of the Russian jewelry industry were conducted. The results unearthed some useful statistical as well as qualitative data. The results from the research highlighted the nascent nature of the Russian Jewelry industry. While the expected growth was promising, the experts felt that there was an acute need for the industry to be organized. Tedious import procedures and duty structures are weighing down the industry. The local producers do not seem to possess the strengths and the skills required for producing the products in demand. Therefore various gaps were noticed for Choron to capitalize on. Also, the emphasis on importing the products from various countries was noted; however, the experts agreed importing products wasn’t their first choice. Apart from this, the big companies (mainly eight) which account for almost 40% of the industry are enjoying their success behind the high entry barriers for new comers created by the import duty structure. The threat from foreign manufacturers could be significant if and when Russia decides to join the WTO. Until then, there seems to be ample scope for manufacturers in Russia. The research also looked at the marketing mix of the main competitors. It was found that mainly companies used the b2b platform for promotion, thus events like tradeshows/ exhibitions were preferred. There is a remarkable absence of advertisement in the b2c space. This enunciates the absence of strong brands. Leaving aside the big luxury brands of the world, the market seems to be devoid of medium to low end brands focusing on the diamond jewelry segment. Thus, the comprehensive research on the Russian jewelry market assisted the formation of the most important aspect of the project, the business plan. 6 MBA‐ Entrepreneurship Management Project‐ Part 1 2009 Business Plan: Based on the Company’s expertise and concluded market research an expansion plan was formulated. This accounted for the Choron’s current stand point and market opportunities. This strategy was further developed into a set of strategic goals that is aimed to get Choron to a market position that it plans for itself. In order to achieve the strategic goals, a set of separate projects each of them contributing to the fulfillment of the Company’s overall strategy was devised. The projects are divided into two parts: Upstream and Downstream projects with two projects in each of the groups. Upstream projects include: • Construction of a new cutting and polishing factory in Yakutsk; • Construction of a jewelry factory in Kostranamo Downstream projects include: • Expansion of current wholesale channels; • Creation of own retail network. For the fulfillment of these aggressive development plans, Choron is looking for strong investors. To finance the expansion Choron will issue USD 120 million preferred stock. The use of proceeds will be as follows: Use of Proceeds Project name Mini Maxi Cutting and polishing factory in Yakutsk $16,000 $22,000 Jewelry factory in Kostroma $ 6,000 $ 8,000 Expansion of wholesale / distribution network $15,000 $25,000 Launch of own retail shops $23,000 $65,000